On the spinor representation - Hoff da Silva, J. M. [UNESP]; Coronado Villalobos, C. H. [UNESP]; Rocha, Roldao da; Bueno Rogerio, R. J. [UNESP] (Springer, 2017)
A systematic study of the spinor representation by means of the fermionic physical space is accomplished and implemented. The spinor representation space is shown to be constrained by the Fierz-Pauli-Kofink identities among the spinor bilinear covariants. A robust geometric and topological structure can be manifested from the spinor space, wherein the first and second homotopy groups play prominent roles on the underlying physical properties, associated to fermionic fields. The mapping that changes spinor fields classes is then exemplified, in an Einstein-Dirac system that provides the spacetime generated by a fermion.